Pre-service teacher's beliefs in mathematics: A systematic literature review 2020-2024 - Yesi Martha Afrillia; Yoppy Wahyu Purnomo (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
A systematic literature review explores research areas related to pre-service teachers' beliefs about Mathematics to consider them in the development of teacher professional education. The articles from Scopus, DOAJ, and ERIC using the PRISMA diagram were extracted, and they included four stages: identification, screening, eligibility, and quality assessment. In total, 26 articles were analyzed. From the analysis, it was found that the country that has conducted the most research on beliefs is Turkey; the method most often used in various studies is quantitative; the characteristics of the sample are mostly prospective mathematics teachers; women dominate the gender of the sample; the construct that appears most often in research is beliefs about teaching mathematics; the instrument most often used is a questionnaire; there are research results from various literatures presented to add insight to readers; and another domain that often appears in research related to pre-service teachers' beliefs about mathematics is self-efficacy. The various research results reveal that women dominate gender issues. It is interesting to explore this topic more deeply, given that men have the same role as women in improving and fostering professionalism.